Social interaction and personal relations / edited by Dorothy Miell and Rudi Dallos - "Miell, Dorothy (ed.)" (London, 1996)
`The team has achieved an admirable overall coherence in representing the range of ideas, methodologies and modes of analysis that will be found in this area of social life.... it is likely to find a place on the reading lists of many future social psychology courses' - Journal of Community and Applied Social Psychology Relationships play a central part in people's lives, and a number of exciting interdisciplinary perspectives have recently emerged to shed new light on what it means to be in a relationship with another human being. This volume offers an authoritative yet accessible examination of a wide variety of these perspectives, drawing from a broader than usual range of material and including considerable reference to clinical contexts and case-studies. Overall, this book provides an introduction to the cutting edge of research about human relationships and interactions, engaging readers in a debate central not only to academic researchers and clinicans but to their own lives. This is the course text for The Open University course Social Psychology: Personal Lives, Social Worlds (D317).
Keywords: Inter personal relations